2003
DOI: 10.1038/sj.npp.1300317
|View full text |Cite
|
Sign up to set email alerts
|

Motor-learning Impairment by Amantadine in Healthy Volunteers

Abstract: NMDA receptor antagonists impair learning and memory in animal models, presumably by inhibiting long-term potentiation in the motor cortex. Human studies are limited and restricted by the paucity of safe NMDA antagonists. Here, we investigated the contribution of glutamatergic neurotransmission to the capacity of acquiring motor-adaptation learning in humans. In a double-blind design, 200 mg of amantadine (a low-affinity NMDA receptor channel blocker) or a matching placebo were given orally to groups of 14 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Modulation of cortical neuroplasticity in humans—the process responsible for learning, memory and repair—stands as a critical learning objective in the fields of clinical neurology and cognitive neuroscience. Classic techniques, such as the use of extracellular stimulation and recording electrodes in animal models and pharmacological modulation of central neurotransmitters in human models, have revealed substantial insights into mechanisms of long‐term plasticity, such as the fundamental role of the synaptic glutamatergic system in inducing long‐term potentiation (LTP) or long‐term depression (LTD) (Bliss, Cooke, Ii, & Cooke, ; Cooke & Bliss, ; Lüscher & Malenka, ; Rowland et al, ; Tahar, Blanchet, & Doyon, ). Moreover, the recent development of noninvasive brain stimulation methods has provided the capability to bi‐directionally modulate and probe these alterations at a system level in a safe and controlled manner (Bikson et al, ; Huang, Lu, et al, ; Stefan, Kunesch, Cohen, Benecke, & Classen, ; Ziemann et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of cortical neuroplasticity in humans—the process responsible for learning, memory and repair—stands as a critical learning objective in the fields of clinical neurology and cognitive neuroscience. Classic techniques, such as the use of extracellular stimulation and recording electrodes in animal models and pharmacological modulation of central neurotransmitters in human models, have revealed substantial insights into mechanisms of long‐term plasticity, such as the fundamental role of the synaptic glutamatergic system in inducing long‐term potentiation (LTP) or long‐term depression (LTD) (Bliss, Cooke, Ii, & Cooke, ; Cooke & Bliss, ; Lüscher & Malenka, ; Rowland et al, ; Tahar, Blanchet, & Doyon, ). Moreover, the recent development of noninvasive brain stimulation methods has provided the capability to bi‐directionally modulate and probe these alterations at a system level in a safe and controlled manner (Bikson et al, ; Huang, Lu, et al, ; Stefan, Kunesch, Cohen, Benecke, & Classen, ; Ziemann et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, many studies have focused on the effects of a common functional polymorphism (Val66Met) in the brain-derived neurotrophic factor (BDNF) gene (Fritsch et al, 2010 ; McHughen et al, 2010 ), a downstream modulator of the molecular cascade supporting synaptic plasticity linked to motor learning impairments and altered motor cortical activations in the plasticity-impaired Met allele carriers (Fritsch et al, 2010 ; McHughen et al, 2010 ; Thomason, Yoo, Glover, & Gotlib, 2009 ). For the evidence in humans, a study by Hadj Tahar et al further showed that the NMDA receptor antagonist amantadine significantly impairs motor learning in healthy subjects (Hadj Tahar, Blanchet, & Doyon, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…2). Other studies have shown that NMDA receptor antagonists may impair retention of many tasks (Miserendino et al, 1990;Olney et al, 1991;Morris et al, 1986;Tahar et al, 2004). Memantine disrupted both memory and locomotor behaviors in rats in high doses (Creeley et al, 2006).…”
Section: Discussionmentioning
confidence: 91%